(untitled) (Journal of Human Sciences, 2021)
This study dealt with the circumstances that led to the conclusion of the Treaty of Ouchy Lausanne, 15 October, 1912, between Italy and the Ottoman Empire - Turkey - as an introduction to study the effect of this agreement on the Libyan jihad movement, and the Ottoman Empire’s failure to surrender Italy to Libya, which prompted it to target the Ottoman Empire in other locations Subordinate to it. This study also dealt with the impact of the agreement on the jihad movement, and this is considered the main focus of the research, which is the negative impact that led to the division in the ranks of the (Mujahedeen) over the way to obtain independence, and this is the goal of everyone, as some saw the need to negotiate with Italy, and others saw the necessity Continuing the jihad to achieve the goal. However, the effect was less negative in the eastern region, given that the Mujahedeen were united around a national leadership represented by Ahmed Al-Sharif. The study also dealt with some national battles such as the battle of Jendouba, which was due to the clear negative impact of the treaty, as the ranks of the Mujahedeen were dispersed, and the battle took place between the Libyans, one against each other, after they were in a single row against Italy, and the battle on Friday that took place in the eastern region between the Mujahedeen and Italy, this battle was mentioned because it had a positive impact on the Mujahedeen, while the impact was negative on Italy, as it stopped their advance to carry out other military operations for a whole month.